Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Solve the equation:
[tex]\[ \begin{array}{l}
3x + 3 = x + 4 \\
3x - x = 4 - 3 \\
2x = 1 \\
x = \frac{1}{2} \\
x = 0.5
\end{array} \][/tex]


Sagot :

Of course! Let's solve the equation [tex]\(3x + 3 = x + 4\)[/tex] step-by-step.

1. First, get all the [tex]\(x\)[/tex] terms on one side of the equation:
[tex]\[ 3x + 3 = x + 4 \][/tex]

2. Subtract [tex]\(x\)[/tex] from both sides to isolate the [tex]\(x\)[/tex] terms on one side:
[tex]\[ 3x - x + 3 = x - x + 4 \][/tex]
Simplify:
[tex]\[ 2x + 3 = 4 \][/tex]

3. Next, get the constant term by itself on the other side:
[tex]\[ 2x + 3 - 3 = 4 - 3 \][/tex]
Simplify:
[tex]\[ 2x = 1 \][/tex]

4. Divide both sides by 2 to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{1}{2} \][/tex]

So, the solution to the equation [tex]\(3x + 3 = x + 4\)[/tex] is:
[tex]\[ x = \frac{1}{2} \text{ or } x = 0.5 \][/tex]

Thus, [tex]\( x = 0.5 \)[/tex] is the correct answer.